SOSIALISASI PERANAN MAUJANA NAGORI DALAM MEMBINA HARMONISASI KEHIDUPAN MASYARAKAT YANG MULTIETNIK DI NAGORI PAMATANG SIMALUNGUN KECAMATAN SIANTAR - Corry Corry; Ulung Napitu; Marhaeni K.D. Matondang; Rosmeri Saragih; Erwin Purba; Ade Mey Lisca Nasution; Desyar Tania Apelin Saragih (Universitas, 2022)
This community service activity aims to describe the role of maujana nagori in fostering harmonization of multiethnic community life in Nagori Pamatang Simalungun, Siantar District. In addition to these objectives, this activity is intended to provide a deep understanding to the community so that they can create a harmonious life, even though the community living in Nagori Pamatang Simalungun is pluralist in terms of ethnicity, religion, race, and between groups. In the implementation of this socialization activity, lecture and question and answer methods were used from the speakers to all community members who attended the socialization. To optimize the socialization activities, the resource persons first consulted with the Head of Nagori so that they could invite the community and set a time for socialization so that the activities could be carried out properly. The results of the socialization activities show that the public's understanding of the importance of the role of Maujana Nagori in realizing the integration and harmonization of pluralist ethnic life in Nagori Pamatang Simalungun, Siantar District is increasing. Besides that, they are also enthusiastic about participating in the socialization and are willing to carry out constructive activities to support development and harmony of life in the midst of a multi-ethnic society